Efektivitas Penggunaan Google Site Sebagai Media Pembelajaran Pada Mata Pelajaran Instalasi Tenaga Listrik - David Hidayatullah; Sukardi Sukardi (Departement of Electrical Engineering Universitas Negeri Padang, 2025)
This study aimed to analyze the effectiveness of using Google Site as a digital learning media in the subject of Electrical Installation for Grade XI TITL students at SMKN 1 Pariaman. This research employed a quantitative approach with a pre-experimental design using the one-group pretest-posttest model. Data were collected through pretest and posttest assessments involving 23 students. The N-Gain Score analysis showed a moderate category of effectiveness with a gain value of 0.574 (57.403%). Paired sample t-test results showed a significant difference (p < 0.05) between pretest and posttest scores, confirming the positive impact of Google Site implementation. The study concludes that Google Site is an effective and accessible platform to enhance students' learning outcomes, particularly in vocational subjects.